A Research Study on Corporate Websites and Social Media in Creating Physical Evidence and Public Strategy MIX - Özkul, Emrah; Bilgili, Bilsen (Archives of Business Research, 2015)
The importance of social media and corporate websites in marketing of service has been increasing day by day with the development of information technologies. The comments about the experience of the service shared in social media, pictures shown the corporate websites as a physical evidence play important role for the branding of services with this study, the investigation of usage strategies of physical evidence is aimed on the purchasement decisions of consumers by decreasing the abstract disadvantage of the service. In this study, 100 hospitality businesses in tourism where sector all elements of service marketing mix used investigated. The factors used as physical evidence corporate websites of hospitality businesses and the comments of experienced consumers in social media create the data of this study. Content analysis had been made with this data. By the comparison of these two types of data, the differences between consumer service quality perception and the elements of physical evidence have been statistically tested. In the parallel of the results obtained in this research, strategic suggestions have been developed for creating successful service brand, marketing of services, creating the loyalty an higher quality perception.